Comparison of Ionic and Diffusive Mass Transport Resistance in Porous Structures. (11th January 2017) - Tjaden, Bernhard; Lane, Jonathan; Neville, Tobias P; Brown, Leon D; Mason, T J; Tan, Chun; Lounasvuori, Mailis M.; Brett, Daniel J.L.; Shearing, Paul R.
Abstract : The tortuosity of a porous structure is commonly used to relate the bulk transport property to an effective transport property. This approach is applied for a wide range of phenomena including charge transport and gas diffusion alike. However, due to the inherent differences between ionic and diffusive transport, the effect of the microstructure on either effective transport property differs. Here, we calculate the tortuosity of a porous membrane via gas diffusion experiments and ionic resistance measurements and compare the results of both techniques. The ionic resistance measurement arrives at lower tortuosity value compared to the gas diffusion measurements. The reason for this might stem from Knudsen diffusion effects, which only affect diffusive mass transport in the gas phase and is affected by the local variation in pore diameter. Hence, Knudsen diffusion effects cannot be neglected in microstructures featuring nano-scale pores.